1977
DOI: 10.1002/mpo.2950030103
|View full text |Cite
|
Sign up to set email alerts
|

Choline antagonism of methotrexate liver toxicity in the rat

Abstract: Because of the frequent reports of hepatic toxicity associated with long-term administration of methotrexate, a rat model was developed utilizing daily methotrexate administration. This model revealed an incidence of fatty metamorphosis of over 80 percent, atrophy and necrosis of 30 percent, and fibrosis of 10 percent. Fatty liver changes did not differ substantially from control animals in those animals receiving long-term thydroxyurea, an agent which, like methotrexate, inhibits DNA synthesis but unlike meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…This finding was in marked contrast to the effect of chronic MTX administration on the hepatic triglyceride content [8,9]. In the present experiment, the chronic administration of 6-MP produced a significant decrease in the hepatic content of triglycerides, and this effect was apparently antagonized by C administration.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding was in marked contrast to the effect of chronic MTX administration on the hepatic triglyceride content [8,9]. In the present experiment, the chronic administration of 6-MP produced a significant decrease in the hepatic content of triglycerides, and this effect was apparently antagonized by C administration.…”
Section: Discussioncontrasting
confidence: 55%
“…In experimental animals, cirrhosis can be induced by a C-deficient diet [6,7]. It has been shown that C can prevent the morphologic and biochemical damage caused by MTX administration in an experimental system suggesting that C deficiency may contribute to the hepatic toxicity of MTX [8,9], 6-MP is metabolized into compounds which both impair the de novo synthesis of purines and interfere with purine interconversion [10]. Theoretically, the hepatic toxicity observed with this drug could also be secondary to C depletion.…”
Section: Introductionmentioning
confidence: 99%
“…15 Choline supplementation reverses the fatty liver caused by methotrexate administration. [16][17][18] Thus, methionine, methyltetrahydrofolate, and choline are fungible sources of methyl groups. The fact that several parallel pathways exist to help ensure an adequate supply of methyl donors demonstrates the physiological importance of these compounds.…”
Section: Choline Folic Acid and Methionine Metabolism Are Relatedmentioning
confidence: 99%
“…Rats treated with methotrexate have diminished pools of all choline metabolites in liver (21). Choline supplementation reverses the fatty liver caused by methotrexate administration (22)(23)(24). Genetically modified mice with defective 5,10-methylene tetrahydrofolate reductase (MTHFR) activity become choline-deficient (25), an important observation because many humans have genetic polymorphisms that alter the activity of this enzyme (26,27).…”
mentioning
confidence: 99%